0D (MoS2)/2D (g-C3N4) heterojunctions in Z-scheme for enhanced photocatalytic and electrochemical hydrogen evolution - Liu, Y.; Zhang, H.; Ke, J.; Zhang, J.; Tian, W.; Xu, X.; Duan, Xiaoguang; Sun, Hongqi; O Tade, M.; Wang, Shaobin (Elsevier BV, 2018)
© 2018 Elsevier B.V. MoS 2 quantum dots (MSQDs) with high and stable dispersion in water were prepared via a facile one-pot hydrothermal process. The MSQDs were then applied to decorate graphitic carbon nitride (g-C 3 N 4 , CN) nanosheets to obtain modified g-C 3 N 4 photocatalysts (MSQD-CN). Compared to pristine g-C 3 N 4 the hybrid photocatalysts showed a slight red shift and stronger light absorption with remarkably improved photocatalytic activity in water splitting to generate hydrogen. The hydrogen-evolution rate over 0.2 wt% MSQD-CN increased by 1.3 and 8.1 times as high as that of 0.2 wt% Pt-CN and g-C 3 N 4 , respectively. With deposition of 2 wt% Pt as a cocatalyst, 5 wt% MSQD-CN exhibited the highest photocatalytic efficiency with an average hydrogen evolution reaction (HER) rate of 577 µmol h -1 g -1 . Photoluminescence spectra (PL) and photoelectrochemical measurements inferred that MSQDs introduction drastically promoted the electron transfer for more efficient separation of charge carriers, which could lower HER overpotential barriers and enhance the electrical conductivity. In addition, the well-matched band potentials of the MSQD-CN hybrid with an intimate contact interface of p-n heterojunction also inhibited the recombination of photo-generated carriers, leading to enhanced photocatalytic HER performance. A direct Z-scheme charge transfer mechanism of the MSQD-CN hybrid was proposed to further elaborate the synergistic effect between MSQDs, Pt and g-C 3 N 4 . This work underlines the importance of heterojunction interface and presents a feasible protocol for rational construction of g-C3N4 based photocatalysts for various photocatalytic applications.